2nd International Geothermal Conference. (March 2019) - Unknown
Abstract : PREFACE 2 nd International Geothermal Conference GEOHEAT 2018 organized by Research Geotechnological Center of Far Eastern Branch of the Russian Academy of Sciences of the Ministry of Science and Higher Education of the Russian Federation, Petropavlovsk-Kamchatsky, Russian Federation was held in Petropavlovsk-Kamchatsky 04-07 September, 2018. There were presented 31 plenary and 21 poster presentations at the Conference. The conference gathered more than 100 participants from different countries. There were reports and posters of the participants from 20 countries (Azerbaijan, Bangladesh, Bulgaria, China, Colombia, Costa Rica, Democratic Republic of the Congo, France, Germany, Indonesia, Kyrgyzstan, Mexico, Russia, Switzerland, Tajikistan, Turkey, Uganda, Ukraine, USA, Yemen Arab Republic). Main Topics for talks, posters, and panel discussions were theoretical issues of geothermics and heat flow, geothermal resources in extensional and compressional settings, geosciences, case studies, exploration, field management, electricity generation, drilling and well bore flows, reservoir engineering and numerical simulation, enhanced geothermal system/hot dry rocks, geology of geothermal fields, geochemistry of geothermal fields, thermal properties of geothermal fields rocks, low enthalpy systems and direct use, geothermal heat pumps, geothermal hydrogen, magma chambers, economics. The event contributed to the solution of a number of fundamental problems: the development of theoretical issues of geothermics and heat flow of the Earth; establishment of new features of thermophysical processes in the geothermal water field development with supercritical thermodynamic parameters; the establishment of geothermal parameters of the Earth crust on basis of advanced experimental technologies (continuous thermal core logging technology, instruments for thermal property measurements at formation conditions, accounting of rocks heterogeneity, as well as micro-and macroanisotropy), and on this basis the geothermal resources revaluation, including geothermal resources maps. The organizing committee consisted of 29 persons from 19 countries. The conference proceedings contain the papers presented at the 2 nd International Geothermal Conference GEOHEAT 2018. Convener, Chair of the Organizing Committee Roman I. Pashkevich